Évaluation de la fraude à l’assurance automobile au Québec - Dionne, Georges; Belhadji, El-Bashir (Assurances, 1996)
This report measures the importance of observed insurance fraud in the Quebec automobile insurance industry. It covers all property damage claims excluding those for “glass damage only”, during the April 1994-March 1995 period. Eighteen (18) insurance companies representing seventy percent (70 %) of the market participated in the survey. Claim adjusters from these companies studied 2 509 closed files in order to get the necessary information to evaluate insurance fraud. Our results indicate that 3 to 6,4 % of all claim payments during the study period contained fraud which represents between 28 to 61 millions of dollars. In absolute terms, these dollar values may seem low but, when compared to the 3,7 millions of direct benefits from fraud fighting obtained from the same data set, they are significant and must be considered seriously by the industry: the estimated fraud represents a minimum since it measures the observed fraud only.